An investigation (Cd + Co) Co-Loading Impact on Physical Properties of Nano-Structured (CuO) Thin Films - Nabeel khalil Husien; J. Alzanganawee (ASJ - Academic Science Journal, 2023)
Pure CuO and (Cd+Co) double doping CuO thin films were produced using the sol- gel method and the spin coating approach, with various (Cd+Co) co-doping concentrations ((1+1), (3+3), (5+5), and (7+7) wt.%) of (Cd+Co). XRD results showed that all prepared pure and metals co-doped CuO nanostructured thin films are polycrystalline and have a monoclinic structure with preferred planes on (002) and (111) without additional peaks related to Cd and Co. The surface morphology and layer thickness of synthesized thin films were analyzed by field emission Scanning Electron Microscopy. The SEM images showed Agglomerated spherical grains form at high co-doping concentrations. The existence of Cu, Cd, Co, and O elements was confirmed by EDS measurements., The energy gap decreased from 2.139eV to 2.02 eV was investigated by the Tauc’s and Davis-Mott relations.